The Portuguese clergy and the European universities in the 12th and 13th centuries - Fleisch, Ingo (2012)
Even before the foundation of the first Portuguese University in Lisbon (1288/89), the Western Iberian region maintained close contacts with the nascent European academic culture. The advance of the Cluniac movement, the penetration of the Iberian Episcopate by French clergymen and the growth of papal influence in the Iberian Peninsula were fundamental for the development of those contacts. During the 12th century Santa Cruz de Coimbra became one of the most dynamic cultural centres of Western Iberia and played an important role in linking the region with the leading French centres of learning. By the end of the century, the influence of Bolognese jurisprudence became more important and offered excellent career opportunities in cathedral chapters, particularly in Northern Portugal. Finally, the newly founded Spanish Universities of Palencia and Salamanca exerted a strong impulse upon Portugal, having a large contribution to the emergence of the first Portuguese University.